Kajian Produktivitas Alat untuk Mengoptimalkan Hasil Produksi Overburden di PT. Karebet Mas Indonesia Site Kutai Energi Kalimantan Timur - Putri, Fairus Atika Redanto; Cahyono, Yudho Dwi Galih; Rabin, Serin (Program Studi Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2021)
Overburden and coal mining must go hand in hand and in line, because high overburden productivity will affect coal production results. This study aims to calculate, analyze productivity and determine recommendations for increasing production. This research uses a combined research method and a mathematical pattern. The company has a productivity target of 220.5 m3/hour, with the actual conditions obtained for digging and loading equipment that has reached the target of 279.9238 BCM/hour, but the transportation equipment has not reached the target of 80.9048 LCM/hour. There are various factors that have not achieved the production target, among others, low work efficiency, quite long transportation and return times during transportation equipment circulation times, as well as mismatched compatibility factors that cause long waiting times for transportation equipment. After optimization with the addition of 1 unit of excavator with the same type, optimization of the transportation equipment cycle time and optimization of the work efficiency of the transportation equipment, an increase in productivity was obtained in each conveyance, so that after optimizing the productivity target of transportation equipment was achieved by 222 ,4045 LCM/Hour.